The magician king : a novel - Grossman, Lev. (London : Viking, 2011)
Quentin and his friends are now the kings and queens of Fillory, but the days and nights of royal luxury are starting to pall. After a morning hunt takes a sinister turn, Quentin and his old friend Julia charter a magical sailing ship and set out on an errand to the wild outer reaches of their kingdom. Their pleasure cruise becomes an adventure when the two are unceremoniously dumped back into the last place Quentin ever wants to see: his parent's house in Chesterton, Massachusetts. And only the black, twisted magic that Julia learned on the streets can save them.
Keywords: Magic -- Fiction; College graduates -- Fiction